DEVELOPMENT OF STEM EDP-BASED SCIENTIFIC ATTITUDE ASSESSMENT INSTRUMENT IN ELEMENTARY SCHOOL SCIENCE LEARNING - Nabila Alisyia Rahman; Din Azwar Uswatun; Astri Sutisnawati (Jurnal Cakrawala Pendas, 2025)
The purpose of this study was to determine the feasibility of the scientific attitude assessment instrument based on the STEM approach with the EDP model in elementary school science learning. This study uses the research and development method. The method used in this development research is based on the Borg & Gall development model. The trial subjects were grade V Al-Khawarizmi V Al-Jazari elementary school students. This study used instruments in the form of questionnaires and observation sheets. The overall validation results from experts reached a percentage of 80.5% with the category "Feasible" and the results from practitioners showed 86.11% with the category "very practical". After the feasibility and practical test of scientific attitude product development, there were 15 valid questions and 0.811 which were stated as very reliable and the observation sheet assessed by the educator showed validity and reliability which showed 0.928. From the results of the needs analysis, the principle of developing a scientific attitude assessment instrument based on the STEM approach with the EDP model in science learning which not only focuses on science learning but the STEM approach that combines four fields of science, namely (Science, Technology, Engineering and Mathematics) this approach involves students in solving real problems, thus encouraging curiosity, objectivity, and cooperation. By using the EDP model, students grow their involvement through the stages of observation, design, testing, and evaluation, which triggers a careful attitude, and critical thinking.